APPLICABILITY OF A LAMINAR FLOW BASED MODEL IN PIPEFLOW MODELLING OF WATER HYDRAULIC SYSTEMS - Leino, Timo; Linjama, Matti; Koskinen, Kari Tapio; Vilenius, Matti Juhani (International Journal of Fluid Power, 2001)
Turbulent flow in pipes is usually avoided in traditional oil hydraulics. However, using water as a hydraulic flu-id, the flow can be regarded as turbulent and the Reynolds number is usually between 10000 and 200000. Most of the pipe models are formed assuming the flow to be as laminar. One pipe model has been developed using a varia-tional method and modal approximation. In this research the applicability of this model to simulate strongly turbu-lent pipe flow has been studied. The comparison between the simulated and measured results is made in time do-main. These results show that this pipe model can be used in practical designing also when the flow is turbulent.